Transformation of Principal Leadership in the Review of Supervisory Functions - Rita Prima Bendriyanti; Citra Dewi; Sukirdi Sukirdi; Suwarni Suwarni (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
This study is grounded in the strategic role of the principal as the primary driver of educational quality improvement through effective supervisory leadership. In the context of rapid technological advancement, evolving educational policies, and increasing accountability demands, principals are required to transform their supervisory approaches from administrative and compliance-oriented practices toward participatory, visionary, and development-focused leadership. This study aims to analyze the level of principal leadership transformation in the supervisory function based on teachers’ and education personnel’s perceptions, and to identify the strongest and weakest implementation indicators. A descriptive quantitative design was employed using a total sampling technique involving 31 respondents at SDN 16 Bengkulu Selatan. Data were collected through a questionnaire consisting of 35 Likert-scale statements and analyzed using descriptive statistics to determine frequency distribution, percentages, and mean scores for each indicator. The findings reveal that most supervisory leadership indicators fall within the good to very good categories. The highest mean scores were observed in exemplary discipline and the principal’s role as an initiator of reform, while the lowest score was found in the indicator related to granting complete freedom without control. These results support Transformational Leadership and Managerial Role theories, highlighting the importance of vision, role modelling, participatory engagement, and structured supervision. The study concludes that supervisory leadership practices are generally aligned with modern leadership principles but require strengthening in post-supervision follow-up mechanisms and in balancing teacher autonomy with appropriate supervisory control. The study contributes a detailed mapping of supervisory indicators grounded in contemporary leadership theory.